2022
DOI: 10.1021/acsomega.2c00336
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Interaction between Polyphenols and β-Lactoglobulin through Molecular Docking, MD Simulation, and QM/MM Approaches

Abstract: In this work, we have explored the interaction of three different polyphenols with the food protein β-lactoglobulin. Antioxidant activities of polyphenols are influenced by complexation with the protein. However, studies have shown that polyphenols after complexation with the protein can be more beneficial due to enhanced antioxidant activities. We have carried out molecular docking, molecular dynamics (MD) simulation, and quantum mechanics/molecular mechanics (QM/MM) studies on the three different protein–pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Further advances in technology and research are expected to continue to unravel the detailed interaction between polyphenols and MMPs. The use of emerging computational technologies including quantum mechanical/molecular mechanical simulations [ 152 , 153 ], may enhance our understanding of precise binding modes and complexation between polyphenols and MMPs.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Further advances in technology and research are expected to continue to unravel the detailed interaction between polyphenols and MMPs. The use of emerging computational technologies including quantum mechanical/molecular mechanical simulations [ 152 , 153 ], may enhance our understanding of precise binding modes and complexation between polyphenols and MMPs.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Furthermore, a number of proteins interact with phenolic compounds and affect milk product properties [ 64 ]. Several studies have demonstrated that proteins can bind to phenolic compounds [ [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] ]. Protein structure can be altered by phenolic compounds binding to proteins, thus affecting availability of certain amino acids [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, a protein can bind different antioxidants at different sites. For example, β-lactoglobulin (BLG) binds apigenin in the internal cavity, luteolin at the entrance of the cavity, and eriodictyol outside the cavity [ 29 ].…”
Section: Binding Characteristics Of Proteins and Their Interaction Wi...mentioning
confidence: 99%